Biological Effects of Ciliary Neurotrophic Factor on hMADS Adipocytes - Perugini, Jessica; Di Mercurio, Eleonora; Tossetta, Giovanni; Severi, Ilenia; Monaco, Federica; Reguzzoni, Marcella; Tomasetti, Marco; Dani, Christian; Cinti, Saverio; Giordano, Antonio (Frontiers in Endocrinology, 2019)
Administration of ciliary neurotrophic factor (CNTF) to experimental animals exerts anti-obesity effects by acting on multiple targets. In white adipose tissue CNTF reduces lipid content, promotes fatty acid (FA) oxidation and improves insulin sensitivity. This study was performed to establish whether CNTF exerts similar effects on human white adipocytes. To this end, adipose differentiation was induced in vitro in human multipotent adipose-derived stem (hMADS) cells. CNTF receptor α (CNTFRα) expression was assessed in hMADS cells and adipocytes by qRT-PCR, Western blotting and immunocytochemistry. After administration of human recombinant CNTF, signalling pathways and gene expression were evaluated by Western blotting and qRT-PCR. Glucose uptake was assessed by measuring 2-nitrobenzodeoxyglucose uptake with a fluorescence plate reader. Lastly, CNTF-induced anti-inflammatory responses were evaluated in hMADS adipocytes stressed with tumour necrosis factor α (TNFα) for 24 h. Results showed that CNTFRα protein expression was higher in undifferentiated hMADS cells than in hMADS adipocytes, where it was however clearly detectable. In hMADS adipocytes, 1 nM CNTF strongly activated the JAK-STAT3 (Janus kinase-signalling transducer and activator of transcription 3) pathway and acutely and transiently activated the AMPK (AMP-activated protein kinase) and AKT (protein kinase B) pathways. Acute CNTF treatment for 20 min significantly increased glucose uptake and was associated with increased AKT phosphorylation. Longer-term (24 and 48 h) treatment reduced the expression of lipogenic markers (FA synthase and sterol regulatory element-binding protein-1) and increased the expression of lipolytic (hormone-sensitive lipase and adipose triglyceride lipase) and mitochondrial (peroxisome proliferator-activated receptor γ coactivator-1α and carnitine palmitoyltransferase 1) markers. In TNFα-treated hMADS adipocytes, CNTF significantly reduced the expression of monocyte chemoattractant protein 1 and TNFα-induced AKT inhibition. Collectively, these findings demonstrate for the first time that CNTF plays a role also in human adipocytes, driving their metabolism towards a less lipid-storing and more energy-consuming phenotype.